Rola treści humorystycznych w procesie glottodydaktycznym. Analiza wybranych podręczników do nauki języka niemieckiego - Wowro, Iwona (Neofilolog, 2019)
The aim of the article is to present the function of humour in teaching/learning, paying particular attention to the specific character of foreign language acquisition. The author presents arguments and concisely describes the most common forms of humour occurring in coursebooks . In the second part of the article the author quotes and briefly discusses some examples of comical elements in German textbooks which are intended for children and young people.